Exploring International Master’s Students’ Perceptions on the Use of Generative AI tools for Academic Writing in Finland - Karnabi, Sfia (My University, 2025)
This thesis explores how international Master’s students in Finland view their use or non-use of generative AI (genAI) tools for academic writing and how they perceive the benefits and drawbacks of this use. By specifically focusing on international Master’s students enrolled in social sciences programs at a university in Finland, this study contributes to research on students’ perspectives on the use of genAI tools in higher education. Semi-structured interviews with users and non-users of genAI tools were analyzed using reflexive thematic analysis, which enabled the identification of key patterns in participants’ perceptions. Drawing on Zimmerman’s model of self-regulated learning, the analysis also examined how students’ perspectives on the use of genAI tools relate to their self-regulation for academic writing. A key finding of this study is that, contrary to common assumptions about students’ primary use of genAI tools to save time, all participants emphasized the importance of using these tools critically. Instead of consistently saving time, they reported to often reallocate or even invest additional time to verify and refine AI-generated content. Furthermore, students’ views and practices were found to be highly context-dependent, influenced not only by peers’ behaviours and university guidelines on AI use but also by their perceptions of teachers’ attitudes toward the use of genAI tools. The findings of this study offer several pedagogical implications for higher education institutions and teachers regarding students’ use of genAI tools. More specifically, they suggest that clearer communication about university guidelines on AI use and more open, constructive dialogue between teachers and students are needed to support more informed and transparent use of genAI tools.
Keywords: generative AI tools (genAI tools), higher education, academic writing, international Master’s students, self-regulated learning, Finland, students’ perspectives